26.3: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/26.3.E1 26.3.E1] || [[Item:Q7774|<math>\binom{m}{n} = \binom{m}{m-n}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \binom{m}{m-n}</syntaxhighlight> || <math>m \geq n</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = binomial(m,m - n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Binomial[m,m - n]</syntaxhighlight> || Failure || Successful || Successful [Tested: 6] || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E1 26.3.E1] || <math qid="Q7774">\binom{m}{n} = \binom{m}{m-n}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \binom{m}{m-n}</syntaxhighlight> || <math>m \geq n</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = binomial(m,m - n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Binomial[m,m - n]</syntaxhighlight> || Failure || Successful || Successful [Tested: 6] || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E1 26.3.E1] || [[Item:Q7774|<math>\binom{m}{m-n} = \frac{m!}{(m-n)!\,n!}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{m-n} = \frac{m!}{(m-n)!\,n!}</syntaxhighlight> || <math>m \geq n</math> || <syntaxhighlight lang=mathematica>binomial(m,m - n) = (factorial(m))/(factorial(m - n)*factorial(n))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,m - n] == Divide[(m)!,(m - n)!*(n)!]</syntaxhighlight> || Successful || Successful || Skip - symbolical successful subtest || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E1 26.3.E1] || <math qid="Q7774">\binom{m}{m-n} = \frac{m!}{(m-n)!\,n!}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{m-n} = \frac{m!}{(m-n)!\,n!}</syntaxhighlight> || <math>m \geq n</math> || <syntaxhighlight lang=mathematica>binomial(m,m - n) = (factorial(m))/(factorial(m - n)*factorial(n))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,m - n] == Divide[(m)!,(m - n)!*(n)!]</syntaxhighlight> || Successful || Successful || Skip - symbolical successful subtest || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E2 26.3.E2] || [[Item:Q7775|<math>\binom{m}{n} = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = 0</syntaxhighlight> || <math>n > m</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == 0</syntaxhighlight> || Failure || Failure || Successful [Tested: 3] || Successful [Tested: 3]
| [https://dlmf.nist.gov/26.3.E2 26.3.E2] || <math qid="Q7775">\binom{m}{n} = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = 0</syntaxhighlight> || <math>n > m</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == 0</syntaxhighlight> || Failure || Failure || Successful [Tested: 3] || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E3 26.3.E3] || [[Item:Q7776|<math>\sum_{n=0}^{m}\binom{m}{n}x^{n} = (1+x)^{m}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{n=0}^{m}\binom{m}{n}x^{n} = (1+x)^{m}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(binomial(m,n)*(x)^(n), n = 0..m) = (1 + x)^(m)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Binomial[m,n]*(x)^(n), {n, 0, m}, GenerateConditions->None] == (1 + x)^(m)</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 0]
| [https://dlmf.nist.gov/26.3.E3 26.3.E3] || <math qid="Q7776">\sum_{n=0}^{m}\binom{m}{n}x^{n} = (1+x)^{m}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{n=0}^{m}\binom{m}{n}x^{n} = (1+x)^{m}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>sum(binomial(m,n)*(x)^(n), n = 0..m) = (1 + x)^(m)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Binomial[m,n]*(x)^(n), {n, 0, m}, GenerateConditions->None] == (1 + x)^(m)</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 0]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E4 26.3.E4] || [[Item:Q7777|<math>\sum_{m=0}^{\infty}\binom{m+n}{m}x^{m} = \frac{1}{(1-x)^{n+1}}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{m=0}^{\infty}\binom{m+n}{m}x^{m} = \frac{1}{(1-x)^{n+1}}</syntaxhighlight> || <math>|x| < 1</math> || <syntaxhighlight lang=mathematica>sum(binomial(m + n,m)*(x)^(m), m = 0..infinity) = (1)/((1 - x)^(n + 1))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Binomial[m + n,m]*(x)^(m), {m, 0, Infinity}, GenerateConditions->None] == Divide[1,(1 - x)^(n + 1)]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/26.3.E4 26.3.E4] || <math qid="Q7777">\sum_{m=0}^{\infty}\binom{m+n}{m}x^{m} = \frac{1}{(1-x)^{n+1}}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\sum_{m=0}^{\infty}\binom{m+n}{m}x^{m} = \frac{1}{(1-x)^{n+1}}</syntaxhighlight> || <math>|x| < 1</math> || <syntaxhighlight lang=mathematica>sum(binomial(m + n,m)*(x)^(m), m = 0..infinity) = (1)/((1 - x)^(n + 1))</syntaxhighlight> || <syntaxhighlight lang=mathematica>Sum[Binomial[m + n,m]*(x)^(m), {m, 0, Infinity}, GenerateConditions->None] == Divide[1,(1 - x)^(n + 1)]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E5 26.3.E5] || [[Item:Q7778|<math>\binom{m}{n} = \binom{m-1}{n}+\binom{m-1}{n-1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \binom{m-1}{n}+\binom{m-1}{n-1}</syntaxhighlight> || <math>m \geq n, n \geq 1</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = binomial(m - 1,n)+binomial(m - 1,n - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Binomial[m - 1,n]+Binomial[m - 1,n - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E5 26.3.E5] || <math qid="Q7778">\binom{m}{n} = \binom{m-1}{n}+\binom{m-1}{n-1}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \binom{m-1}{n}+\binom{m-1}{n-1}</syntaxhighlight> || <math>m \geq n, n \geq 1</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = binomial(m - 1,n)+binomial(m - 1,n - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Binomial[m - 1,n]+Binomial[m - 1,n - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E6 26.3.E6] || [[Item:Q7779|<math>\binom{m}{n} = \frac{m}{n}\binom{m-1}{n-1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \frac{m}{n}\binom{m-1}{n-1}</syntaxhighlight> || <math>m \geq n, n \geq 1</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = (m)/(n)*binomial(m - 1,n - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Divide[m,n]*Binomial[m - 1,n - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E6 26.3.E6] || <math qid="Q7779">\binom{m}{n} = \frac{m}{n}\binom{m-1}{n-1}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \frac{m}{n}\binom{m-1}{n-1}</syntaxhighlight> || <math>m \geq n, n \geq 1</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = (m)/(n)*binomial(m - 1,n - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Divide[m,n]*Binomial[m - 1,n - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E6 26.3.E6] || [[Item:Q7779|<math>\frac{m}{n}\binom{m-1}{n-1} = \frac{m-n+1}{n}\binom{m}{n-1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{m}{n}\binom{m-1}{n-1} = \frac{m-n+1}{n}\binom{m}{n-1}</syntaxhighlight> || <math>m \geq n, n \geq 1</math> || <syntaxhighlight lang=mathematica>(m)/(n)*binomial(m - 1,n - 1) = (m - n + 1)/(n)*binomial(m,n - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[m,n]*Binomial[m - 1,n - 1] == Divide[m - n + 1,n]*Binomial[m,n - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E6 26.3.E6] || <math qid="Q7779">\frac{m}{n}\binom{m-1}{n-1} = \frac{m-n+1}{n}\binom{m}{n-1}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{m}{n}\binom{m-1}{n-1} = \frac{m-n+1}{n}\binom{m}{n-1}</syntaxhighlight> || <math>m \geq n, n \geq 1</math> || <syntaxhighlight lang=mathematica>(m)/(n)*binomial(m - 1,n - 1) = (m - n + 1)/(n)*binomial(m,n - 1)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[m,n]*Binomial[m - 1,n - 1] == Divide[m - n + 1,n]*Binomial[m,n - 1]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E7 26.3.E7] || [[Item:Q7780|<math>\binom{m+1}{n+1} = \sum_{k=n}^{m}\binom{k}{n}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m+1}{n+1} = \sum_{k=n}^{m}\binom{k}{n}</syntaxhighlight> || <math>m \geq n, n \geq 0</math> || <syntaxhighlight lang=mathematica>binomial(m + 1,n + 1) = sum(binomial(k,n), k = n..m)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m + 1,n + 1] == Sum[Binomial[k,n], {k, n, m}, GenerateConditions->None]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E7 26.3.E7] || <math qid="Q7780">\binom{m+1}{n+1} = \sum_{k=n}^{m}\binom{k}{n}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m+1}{n+1} = \sum_{k=n}^{m}\binom{k}{n}</syntaxhighlight> || <math>m \geq n, n \geq 0</math> || <syntaxhighlight lang=mathematica>binomial(m + 1,n + 1) = sum(binomial(k,n), k = n..m)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m + 1,n + 1] == Sum[Binomial[k,n], {k, n, m}, GenerateConditions->None]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 6]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E8 26.3.E8] || [[Item:Q7781|<math>\binom{m}{n} = \sum_{k=0}^{n}\binom{m-n-1+k}{k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \sum_{k=0}^{n}\binom{m-n-1+k}{k}</syntaxhighlight> || <math>m \geq n, n \geq 0</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = sum(binomial(m - n - 1 + k,k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Sum[Binomial[m - n - 1 + k,k], {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Successful || Successful || - || <div class="toccolours mw-collapsible mw-collapsed">Failed [3 / 6]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Indeterminate
| [https://dlmf.nist.gov/26.3.E8 26.3.E8] || <math qid="Q7781">\binom{m}{n} = \sum_{k=0}^{n}\binom{m-n-1+k}{k}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \sum_{k=0}^{n}\binom{m-n-1+k}{k}</syntaxhighlight> || <math>m \geq n, n \geq 0</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = sum(binomial(m - n - 1 + k,k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Sum[Binomial[m - n - 1 + k,k], {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Successful || Successful || - || <div class="toccolours mw-collapsible mw-collapsed">Failed [3 / 6]<div class="mw-collapsible-content"><syntaxhighlight lang=mathematica>Result: Indeterminate
Test Values: {Rule[m, 1], Rule[n, 1]}</syntaxhighlight><br><syntaxhighlight lang=mathematica>Result: Indeterminate
Test Values: {Rule[m, 1], Rule[n, 1]}</syntaxhighlight><br><syntaxhighlight lang=mathematica>Result: Indeterminate
Test Values: {Rule[m, 2], Rule[n, 2]}</syntaxhighlight><br>... skip entries to safe data</div></div>
Test Values: {Rule[m, 2], Rule[n, 2]}</syntaxhighlight><br>... skip entries to safe data</div></div>
|-  
|-  
| [https://dlmf.nist.gov/26.3.E9 26.3.E9] || [[Item:Q7782|<math>\binom{n}{0} = \binom{n}{n}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{n}{0} = \binom{n}{n}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>binomial(n,0) = binomial(n,n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[n,0] == Binomial[n,n]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/26.3.E9 26.3.E9] || <math qid="Q7782">\binom{n}{0} = \binom{n}{n}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{n}{0} = \binom{n}{n}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>binomial(n,0) = binomial(n,n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[n,0] == Binomial[n,n]</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E9 26.3.E9] || [[Item:Q7782|<math>\binom{n}{n} = 1</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{n}{n} = 1</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>binomial(n,n) = 1</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[n,n] == 1</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
| [https://dlmf.nist.gov/26.3.E9 26.3.E9] || <math qid="Q7782">\binom{n}{n} = 1</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{n}{n} = 1</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>binomial(n,n) = 1</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[n,n] == 1</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 3]
|-  
|-  
| [https://dlmf.nist.gov/26.3.E10 26.3.E10] || [[Item:Q7783|<math>\binom{m}{n} = \sum_{k=0}^{n}(-1)^{n-k}\binom{m+1}{k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \sum_{k=0}^{n}(-1)^{n-k}\binom{m+1}{k}</syntaxhighlight> || <math>m \geq n, n \geq 0</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = sum((- 1)^(n - k)*binomial(m + 1,k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Sum[(- 1)^(n - k)*Binomial[m + 1,k], {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Successful || Failure || - || Successful [Tested: 6]
| [https://dlmf.nist.gov/26.3.E10 26.3.E10] || <math qid="Q7783">\binom{m}{n} = \sum_{k=0}^{n}(-1)^{n-k}\binom{m+1}{k}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\binom{m}{n} = \sum_{k=0}^{n}(-1)^{n-k}\binom{m+1}{k}</syntaxhighlight> || <math>m \geq n, n \geq 0</math> || <syntaxhighlight lang=mathematica>binomial(m,n) = sum((- 1)^(n - k)*binomial(m + 1,k), k = 0..n)</syntaxhighlight> || <syntaxhighlight lang=mathematica>Binomial[m,n] == Sum[(- 1)^(n - k)*Binomial[m + 1,k], {k, 0, n}, GenerateConditions->None]</syntaxhighlight> || Successful || Failure || - || Successful [Tested: 6]
|}
|}
</div>
</div>

Latest revision as of 12:05, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
26.3.E1 ( m n ) = ( m m - n ) binomial 𝑚 𝑛 binomial 𝑚 𝑚 𝑛 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{n}=\genfrac{(}{)}{0.0pt% }{}{m}{m-n}}}
\binom{m}{n} = \binom{m}{m-n}
m n 𝑚 𝑛 {\displaystyle{\displaystyle m\geq n}}
binomial(m,n) = binomial(m,m - n)
Binomial[m,n] == Binomial[m,m - n]
Failure Successful Successful [Tested: 6] Successful [Tested: 6]
26.3.E1 ( m m - n ) = m ! ( m - n ) ! n ! binomial 𝑚 𝑚 𝑛 𝑚 𝑚 𝑛 𝑛 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{m-n}=\frac{m!}{(m-n)!\,% n!}}}
\binom{m}{m-n} = \frac{m!}{(m-n)!\,n!}
m n 𝑚 𝑛 {\displaystyle{\displaystyle m\geq n}}
binomial(m,m - n) = (factorial(m))/(factorial(m - n)*factorial(n))
Binomial[m,m - n] == Divide[(m)!,(m - n)!*(n)!]
Successful Successful Skip - symbolical successful subtest Successful [Tested: 6]
26.3.E2 ( m n ) = 0 binomial 𝑚 𝑛 0 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{n}=0}}
\binom{m}{n} = 0
n > m 𝑛 𝑚 {\displaystyle{\displaystyle n>m}}
binomial(m,n) = 0
Binomial[m,n] == 0
Failure Failure Successful [Tested: 3] Successful [Tested: 3]
26.3.E3 n = 0 m ( m n ) x n = ( 1 + x ) m superscript subscript 𝑛 0 𝑚 binomial 𝑚 𝑛 superscript 𝑥 𝑛 superscript 1 𝑥 𝑚 {\displaystyle{\displaystyle\sum_{n=0}^{m}\genfrac{(}{)}{0.0pt}{}{m}{n}x^{n}=(% 1+x)^{m}}}
\sum_{n=0}^{m}\binom{m}{n}x^{n} = (1+x)^{m}

sum(binomial(m,n)*(x)^(n), n = 0..m) = (1 + x)^(m)
Sum[Binomial[m,n]*(x)^(n), {n, 0, m}, GenerateConditions->None] == (1 + x)^(m)
Successful Successful - Successful [Tested: 0]
26.3.E4 m = 0 ( m + n m ) x m = 1 ( 1 - x ) n + 1 superscript subscript 𝑚 0 binomial 𝑚 𝑛 𝑚 superscript 𝑥 𝑚 1 superscript 1 𝑥 𝑛 1 {\displaystyle{\displaystyle\sum_{m=0}^{\infty}\genfrac{(}{)}{0.0pt}{}{m+n}{m}% x^{m}=\frac{1}{(1-x)^{n+1}}}}
\sum_{m=0}^{\infty}\binom{m+n}{m}x^{m} = \frac{1}{(1-x)^{n+1}}
| x | < 1 𝑥 1 {\displaystyle{\displaystyle|x|<1}}
sum(binomial(m + n,m)*(x)^(m), m = 0..infinity) = (1)/((1 - x)^(n + 1))
Sum[Binomial[m + n,m]*(x)^(m), {m, 0, Infinity}, GenerateConditions->None] == Divide[1,(1 - x)^(n + 1)]
Successful Successful - Successful [Tested: 3]
26.3.E5 ( m n ) = ( m - 1 n ) + ( m - 1 n - 1 ) binomial 𝑚 𝑛 binomial 𝑚 1 𝑛 binomial 𝑚 1 𝑛 1 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{n}=\genfrac{(}{)}{0.0pt% }{}{m-1}{n}+\genfrac{(}{)}{0.0pt}{}{m-1}{n-1}}}
\binom{m}{n} = \binom{m-1}{n}+\binom{m-1}{n-1}
m n , n 1 formulae-sequence 𝑚 𝑛 𝑛 1 {\displaystyle{\displaystyle m\geq n,n\geq 1}}
binomial(m,n) = binomial(m - 1,n)+binomial(m - 1,n - 1)
Binomial[m,n] == Binomial[m - 1,n]+Binomial[m - 1,n - 1]
Successful Successful - Successful [Tested: 6]
26.3.E6 ( m n ) = m n ( m - 1 n - 1 ) binomial 𝑚 𝑛 𝑚 𝑛 binomial 𝑚 1 𝑛 1 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{n}=\frac{m}{n}\genfrac{% (}{)}{0.0pt}{}{m-1}{n-1}}}
\binom{m}{n} = \frac{m}{n}\binom{m-1}{n-1}
m n , n 1 formulae-sequence 𝑚 𝑛 𝑛 1 {\displaystyle{\displaystyle m\geq n,n\geq 1}}
binomial(m,n) = (m)/(n)*binomial(m - 1,n - 1)
Binomial[m,n] == Divide[m,n]*Binomial[m - 1,n - 1]
Successful Successful - Successful [Tested: 6]
26.3.E6 m n ( m - 1 n - 1 ) = m - n + 1 n ( m n - 1 ) 𝑚 𝑛 binomial 𝑚 1 𝑛 1 𝑚 𝑛 1 𝑛 binomial 𝑚 𝑛 1 {\displaystyle{\displaystyle\frac{m}{n}\genfrac{(}{)}{0.0pt}{}{m-1}{n-1}=\frac% {m-n+1}{n}\genfrac{(}{)}{0.0pt}{}{m}{n-1}}}
\frac{m}{n}\binom{m-1}{n-1} = \frac{m-n+1}{n}\binom{m}{n-1}
m n , n 1 formulae-sequence 𝑚 𝑛 𝑛 1 {\displaystyle{\displaystyle m\geq n,n\geq 1}}
(m)/(n)*binomial(m - 1,n - 1) = (m - n + 1)/(n)*binomial(m,n - 1)
Divide[m,n]*Binomial[m - 1,n - 1] == Divide[m - n + 1,n]*Binomial[m,n - 1]
Successful Successful - Successful [Tested: 6]
26.3.E7 ( m + 1 n + 1 ) = k = n m ( k n ) binomial 𝑚 1 𝑛 1 superscript subscript 𝑘 𝑛 𝑚 binomial 𝑘 𝑛 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m+1}{n+1}=\sum_{k=n}^{m}% \genfrac{(}{)}{0.0pt}{}{k}{n}}}
\binom{m+1}{n+1} = \sum_{k=n}^{m}\binom{k}{n}
m n , n 0 formulae-sequence 𝑚 𝑛 𝑛 0 {\displaystyle{\displaystyle m\geq n,n\geq 0}}
binomial(m + 1,n + 1) = sum(binomial(k,n), k = n..m)
Binomial[m + 1,n + 1] == Sum[Binomial[k,n], {k, n, m}, GenerateConditions->None]
Successful Successful - Successful [Tested: 6]
26.3.E8 ( m n ) = k = 0 n ( m - n - 1 + k k ) binomial 𝑚 𝑛 superscript subscript 𝑘 0 𝑛 binomial 𝑚 𝑛 1 𝑘 𝑘 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{n}=\sum_{k=0}^{n}% \genfrac{(}{)}{0.0pt}{}{m-n-1+k}{k}}}
\binom{m}{n} = \sum_{k=0}^{n}\binom{m-n-1+k}{k}
m n , n 0 formulae-sequence 𝑚 𝑛 𝑛 0 {\displaystyle{\displaystyle m\geq n,n\geq 0}}
binomial(m,n) = sum(binomial(m - n - 1 + k,k), k = 0..n)
Binomial[m,n] == Sum[Binomial[m - n - 1 + k,k], {k, 0, n}, GenerateConditions->None]
Successful Successful -
Failed [3 / 6]
Result: Indeterminate
Test Values: {Rule[m, 1], Rule[n, 1]}

Result: Indeterminate
Test Values: {Rule[m, 2], Rule[n, 2]}

... skip entries to safe data
26.3.E9 ( n 0 ) = ( n n ) binomial 𝑛 0 binomial 𝑛 𝑛 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{n}{0}=\genfrac{(}{)}{0.0pt% }{}{n}{n}}}
\binom{n}{0} = \binom{n}{n}

binomial(n,0) = binomial(n,n)
Binomial[n,0] == Binomial[n,n]
Successful Successful - Successful [Tested: 3]
26.3.E9 ( n n ) = 1 binomial 𝑛 𝑛 1 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{n}{n}=1}}
\binom{n}{n} = 1

binomial(n,n) = 1
Binomial[n,n] == 1
Successful Successful - Successful [Tested: 3]
26.3.E10 ( m n ) = k = 0 n ( - 1 ) n - k ( m + 1 k ) binomial 𝑚 𝑛 superscript subscript 𝑘 0 𝑛 superscript 1 𝑛 𝑘 binomial 𝑚 1 𝑘 {\displaystyle{\displaystyle\genfrac{(}{)}{0.0pt}{}{m}{n}=\sum_{k=0}^{n}(-1)^{% n-k}\genfrac{(}{)}{0.0pt}{}{m+1}{k}}}
\binom{m}{n} = \sum_{k=0}^{n}(-1)^{n-k}\binom{m+1}{k}
m n , n 0 formulae-sequence 𝑚 𝑛 𝑛 0 {\displaystyle{\displaystyle m\geq n,n\geq 0}}
binomial(m,n) = sum((- 1)^(n - k)*binomial(m + 1,k), k = 0..n)
Binomial[m,n] == Sum[(- 1)^(n - k)*Binomial[m + 1,k], {k, 0, n}, GenerateConditions->None]
Successful Failure - Successful [Tested: 6]